The stroke detections scales for emergency response workers: a comparison of FAST versus BEFAST - Tippayanate, Nantawan; Phonkanya, Phatcharee; Nuangkantee, Kanokwan; Nuangkantee, Kamonchanok; Wijanjit, Rungthiwa; Khamya, Ajchra; Chaiprom, Kiattisak; Sriprow, Juntana; Sripol, Chattarin; Tornsao, Maitree (International Journal Of Community Medicine And Public Health, 2022)
Background: Eighty percent of strokes are ischemic, resulting from cerebral artery blockages. However, due to delays in taking patients to hospital, only around 3% of patients receive suitable treatment in time. Methods: This research assessed the accuracy of diagnostic tests. Registry data concerning stroke patients were analyzed to compare the diagnoses made during the dispatching of suspected stroke patients with the final diagnoses made by hospital emergency departments in order to evaluate the validity of the initial tests. Results: The study investigated a sample group of 317 patients. Over fifty percent lived in rural locations. The stroke patients tended to be of more advanced age, and presented significantly more underlying conditions than non-stroke patients (p<0.05). The data were collected over a period of one year, and the scale used was predominantly the BEFAST. Between stroke and non-stroke patients, significant differences were found only in terms of facial drooping and weakened arms (p<0.05). The accuracy levels of the BEFAST and FAST scales could be considered similar when comparing the area under the curve. BEFAST had AUC of 0.551 while for FAST the value was 0.706 (p=0.059). Conclusions: It is possible to increase the sensitivity of BEFAST by including testing for coordination and diplopia, but the results in lowered PPV and specificity. Given that additional time is necessary in order to test coordination and diplopia, it would appear unlikely that this delay during dispatch will be beneficial even when improved sensitivity is taken into account.